Expression of proteins associated with the Warburg‐effect and survival in colorectal cancer. (17th November 2021) - Offermans, Kelly; Jenniskens, Josien CA; Simons, Colinda CJM; Samarska, Iryna; Fazzi, Gregorio E; Smits, Kim M; Schouten, Leo J; Weijenberg, Matty P; Grabsch, Heike I; van den Brandt, Piet A
Abstract: Previous research has suggested that the expression of proteins related to the Warburg effect may have prognostic value in colorectal cancer (CRC), but results remain inconsistent. Our objective was to investigate the relationship between Warburg‐subtypes and patient survival in a large population‐based series of CRC patients. In the present study, we investigated the expression of six proteins related to the Warburg effect (LDHA, GLUT1, MCT4, PKM2, p53, PTEN) by immunohistochemistry on tissue microarrays (TMAs) from 2, 399 incident CRC patients from the prospective Netherlands Cohort Study. Expression levels of the six proteins were combined into a pathway‐based sum‐score and patients were categorised into three Warburg‐subtypes (low/moderate/high). The associations between Warburg‐subtypes and CRC‐specific and overall survival were investigated using Kaplan–Meier curves and Cox regression models. CRC patients were classified as Warburg‐low ( n = 695, 29.0%), Warburg‐moderate ( n = 858, 35.8%) or Warburg‐high ( n = 841, 35.1%). Patients with Warburg‐high CRC had the poorest CRC‐specific [hazard ratio (HR) 1.17; 95% CI 1.00–1.38] and overall survival (HR 1.19; 95% CI 1.05–1.35), independent of known prognostic factors. In stratified analyses, this was particularly true for patients with tumour‐node‐metastasis (TNM) stage III CRC (HRCRC‐specific 1.45; 95% CI 1.10–1.92 and HRoverall 1.47; 95% CI 1.15–1.87), and cancers located in the rectum (HRoverall 1.56; 95% CI 1.15–2.13). To our knowledge, this is the first study to identify the prognostic value of immunohistochemistry‐based Warburg‐subtypes in CRC. Our data suggest that Warburg‐subtypes are related to potentially important differences in CRC survival. Further research is required to validate our findings and to investigate the potential clinical utility of these Warburg‐subtypes in CRC.